2016
DOI: 10.1371/journal.pone.0159542
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity between Schistosoma mansoni Antigens and the Latex Allergen Hev b 7: Putative Implication of Cross-Reactive Carbohydrate Determinants (CCDs)

Abstract: IgG antibodies produced by rabbits immunized against S. mansoni antigens cross-reacted with aqueous soluble constituents of a variety of allergens. The antibody cross-reactivity was largely sensitive to degradation by treatment of the target antigens with sodium meta-periodate, suggesting the cross-reactivity was due to carbohydrate determinants that were common to both the schistosome and the allergens (CCDs). The reaction between the rabbit antibodies and a 43 kDa molecule in a rubber latex extract was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 88 publications
(100 reference statements)
1
34
0
Order By: Relevance
“…Results in Fig. confirm the earlier indications that extensive IgG cross‐reactivity occurs between S. mansoni and peanut antigens/allergens. The non‐reactivity of the anti‐SmSEA antibodies against any of the antigens/molecules in the three tissue extracts from mouse is an indication that the cross‐reactivity of the purified antibodies with antigens in extracts of peanut and those in other plants with potential to cause allergy in humans is not a ubiquitous property of rabbit sera in general.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results in Fig. confirm the earlier indications that extensive IgG cross‐reactivity occurs between S. mansoni and peanut antigens/allergens. The non‐reactivity of the anti‐SmSEA antibodies against any of the antigens/molecules in the three tissue extracts from mouse is an indication that the cross‐reactivity of the purified antibodies with antigens in extracts of peanut and those in other plants with potential to cause allergy in humans is not a ubiquitous property of rabbit sera in general.…”
Section: Discussionsupporting
confidence: 89%
“…We have previously demonstrated that rabbit anti‐schistosome IgG antibodies cross‐react with many different constituents of plants and invertebrates that are allergic to humans . The cross‐reactivity between S. mansoni egg and cercarial antigens and a 43 000 MW molecule in natural rubber latex was investigated in detail and the latter was found to be latex allergen Hev b 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of anti‐ Ascaris IgG4 have been negatively associated with allergen SPT positivity, while in a S. mansoni ‐endemic area—although higher levels of both IgE and IgG4 were found in infected individuals—a higher ratio of IgE to IgG4 predicted clinical allergic symptoms, just as in allergen‐specific immunotherapy . As many helminth products are homologous to common allergens, IgG4 responses raised against helminth products may also bind and block IgE epitopes on allergens, reducing responses to allergens and directly reducing SPT responses . Mechanistic research into the role of IgE and/or IgG4 is hampered by the lack of good experimental animal models, as IgG4 does not exist in mice.…”
Section: Helminths and Modulation Of Allergic Disease: The Role Of Immentioning
confidence: 99%